PENERAPAN GIVING QUESTIONS AND GETTING ANSWER (GQGA) BERBANTUAN PODCAST UNTUK MENINGKATKAN HASIL BELAJAR ETIKA PROFESI - Anggi Tiya Ramadhani; siswandari siswandari; Nurhasan Hamidi (Jurnal Pengembangan Pendidikan Akuntansi dan Keuangan (JPPAK), 2021)
AbstractThe purpose of this research is to improve the learning outcomes of cognitive and affective aspects in the subject of accounting professional ethics through the application of the GQGA learning strategy assisted by podcast media class X Accounting at SMK. This research is a classroom action research conducted in two cycles. Each cycle consists of planning, implementing, observing and reflecting. The subjects of this study were 20 students of class X AKL SMK. The data collection techniques used were tests, questionnaires, observation and documentation. Content validity is used to test the validity of the generating data. The data analysis technique used is descriptive qualitative analysis techniques and quantitative descriptive analysis. The results of this study concluded that the learning outcomes of accounting profession ethics in cognitive and affective aspects of class X AKL students at SMK increased after the application of the GQGA learning strategy assisted by podcast media. The percentage of achievement indicators of learning outcomes in the cognitive aspects increased by 45% (from 40% to 85%) and the average score of learning outcomes in the cognitive aspects increased by 20 points (from 56.5 to 81.5) in cycle II. Meanwhile, the percentage of learning outcomes in the affective aspect increased by 55% in the high category (from 25% to 80%) and the average score of learning outcomes in the affective aspect increased by 15 points (from 42.9 to 58.25) in the second cycle. This increase was statistically significant at α = 0.05 with t = 3.889 (p-value 0.001) for cognitive aspects and t = 5.358 (p-value 0.000) for affective aspects.  Keyword: Learning Outcomes, GQGA, Podcast.AbstrakTujuan penelitian ini adalah untuk meningkatkan hasil belajar aspek kognitif dan aspek afektif pada mata pelajaran etika profesi akuntansi dengan penerapan strategi pembelajaran GQGA berbantuan media podcast kelas X Akuntansi di SMK. Penelitian ini merupakan penelitian tindakan kelas yang dilaksanakan sebanyak dua siklus. Setiap siklus terdiri dari perencanaan, pelaksanaan, observasi dan refleksi. Subjek penelitian ini adalah siswa kelas X AKL SMK yang berjumlah 20 siswa. Teknik pengumpulan data yang digunakan adalah tes, angket, observasi dan dokumentasi. Validitas isi digunakan untuk menguji validitas data yang dihasilkan. Teknik analisis data yang digunakan adalah teknik analisis deskriptif kualitatif dan analisis deskriptif kuantitatif. Hasil penelitian ini menyimpulkan bahwa hasil belajar etika profesi akuntansi aspek kognitif dan aspek afektif siswa kelas X AKL di SMK meningkat setelah penerapan strategi pembelajaran GQGA berbantuan media podcast. Persentase capaian indikator hasil belajar aspek kognitif meningkat 45% (dari 40% menjadi 85%) dan skor rata-rata hasil belajar aspek kognitif meningkat 20 poin (dari 56,5 menjadi 81,5) pada siklus II. Sementara, persentase capaian indikator hasil belajar aspek afektif meningkat 55% dengan kategori tinggi (dari 25% menjadi 80%) dan skor rata-rata hasil belajar aspek afektif meningkat 15 poin (dari 42,9 menjadi 58,25) pada siklus II. Peningkatan tersebut signifikan secara statistik pada α = 0,05 dengan t = 3,889 (p-value 0,001) untuk aspek kognitif dan t = 5,358 (p-value 0,000) untuk aspek afektif.Kata kunci: Hasil Belajar, GQGA, Podcast.